2007
DOI: 10.1038/ncb1656
|View full text |Cite
|
Sign up to set email alerts
|

SNX4 coordinates endosomal sorting of TfnR with dynein-mediated transport into the endocytic recycling compartment

Abstract: SNX-BAR proteins are a sub-family of sorting nexins implicated in endosomal sorting. Here, we establish that through its phox homology (PX) and Bin-Amphiphysin-Rvs (BAR) domains, sorting nexin-4 (SNX4) is associated with tubular and vesicular elements of a compartment that overlaps with peripheral early endosomes and the juxtanuclear endocytic recycling compartment (ERC). Suppression of SNX4 perturbs transport between these compartments and causes lysosomal degradation of the transferrin receptor (TfnR). Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
288
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(316 citation statements)
references
References 41 publications
17
288
2
5
Order By: Relevance
“…30 -32 In addition to the putative indirect association to the actin cytoskeleton, it has been demonstrated that KIBRA directly binds to dynein light chain 1 (DLC1) and sorting nexin 4 (SNX4). 38,39 The DLC1-SNX4-KIBRA complex associates with the minus-end directed microtubule motor dynein complex. 38 These studies support our observation that KIBRA at least indirectly associates with the microtubule network; therefore, KIBRA might act as a bridge between actin-and/or microtubule-associated networks and cell polarity complexes.…”
Section: Discussionmentioning
confidence: 99%
“…30 -32 In addition to the putative indirect association to the actin cytoskeleton, it has been demonstrated that KIBRA directly binds to dynein light chain 1 (DLC1) and sorting nexin 4 (SNX4). 38,39 The DLC1-SNX4-KIBRA complex associates with the minus-end directed microtubule motor dynein complex. 38 These studies support our observation that KIBRA at least indirectly associates with the microtubule network; therefore, KIBRA might act as a bridge between actin-and/or microtubule-associated networks and cell polarity complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that cytoskeletons have profound roles guiding and segregating membrane trafficking intermediates (5,(47)(48)(49). To further unravel the machinery underlying the dynamic hTAC tubules, we tested their dependence on the cytoskeleton.…”
Section: The Generation Of Htac-positive Tubules Requires Microtubulementioning
confidence: 99%
“…SNX3 binds to PI(3)P [16] and is required for biogenesis of endocytic carrier vesicles/multivesicular bodies [17]. SNX4 associates with dynein/dynactin through its interaction with the dynein light chain 1-binding protein KIBRA and is required for transport of the transferrin receptor between peripheral early endosomes and the juxtanuclear endocytic recycling compartment [18]. SNX9, in contrast, senses phosphatidylinositol 4,5-bisphosphate signals at the plasma membrane and couples actin dynamics with membrane remodeling during clathrin-mediated endocytosis, dorsal ruffle formation and clathrin-independent fluid phase endocytosis [19].…”
Section: Introductionmentioning
confidence: 99%